Respuesta :
Answer:
-27
Step-by-step explanation:
9(4x – 15)
Substitute 3 for x
9((4)(3) - 15)
Multiply (4)(3) = 12
9 ( 12 - 15 )
Subtract 12 - 15 = -3
9(-3)
Multiply 9(-3) = -27
[tex]\implies {\blue {\boxed {\boxed {\purple {\sf {-27}}}}}}[/tex]
[tex]\large\mathfrak{{\pmb{\underline{\red{Step-by-step\:explanation}}{\red{:}}}}}[/tex]
[tex] \: 9 \: (4x - 15)[/tex]
Plugging in the value [tex]x = 3[/tex] in the above expression, we have
➼ [tex] \: 9 \: (4 \times 3 - 15)[/tex]
➼ [tex] \: 9 \: (12 - 15)[/tex]
➼ [tex] \: 9 \: ( - 3)[/tex]
➼ [tex] \: - 27[/tex]
Note:-
[tex]\sf\pink{PEMDAS\: rule.}[/tex]
P = Parentheses
E = Exponents
M = Multiplication
D = Division
A = Addition
S = Subtraction
[tex]\large\mathfrak{{\pmb{\underline{\orange{Mystique35 }}{\orange{❦}}}}}[/tex]